2007
DOI: 10.1085/jgp.200609729
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Properties of Rod Photoreceptor Cells in Green-sensitive Cone Pigment Knock-in Mice

Abstract: Rod and cone photoreceptor cells that are responsible for scotopic and photopic vision, respectively, exhibit photoresponses different from each other and contain similar phototransduction proteins with distinctive molecular properties. To investigate the contribution of the different molecular properties of visual pigments to the responses of the photoreceptor cells, we have generated knock-in mice in which rod visual pigment (rhodopsin) was replaced with mouse green-sensitive cone visual pigment (mouse green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
52
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 55 publications
8
52
1
1
Order By: Relevance
“…At 37°C, V max /R* of mRh (38.8 G t */s) was about 2.5-fold greater than that of mG (15.4 G t */s). This difference in G t activation efficiency is consistent with our previous electrophysiological study (7), which showed that the amplification efficiency of mRh was about 3-fold greater than that of mG. Therefore, it is likely that the difference in G t activation efficiency between rhodopsin and cone visual pigments was the main contributor to the difference in the amplification efficiency of the single photon response in that previous study.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…At 37°C, V max /R* of mRh (38.8 G t */s) was about 2.5-fold greater than that of mG (15.4 G t */s). This difference in G t activation efficiency is consistent with our previous electrophysiological study (7), which showed that the amplification efficiency of mRh was about 3-fold greater than that of mG. Therefore, it is likely that the difference in G t activation efficiency between rhodopsin and cone visual pigments was the main contributor to the difference in the amplification efficiency of the single photon response in that previous study.…”
Section: Resultssupporting
confidence: 91%
“…It has been reported previously that the G t activation efficiencies of rhodopsin and cone visual pigments were similar to each other based on experiments performed at about 0°C (7,9,10), although those of rhodopsin and cone visual pigments of a poikilothermic animal (carp) were recently reported to be different at 20°C (11,12). Thus, it is likely that the difference in amplification efficiency between wild-type rods and rods con-taining mG is caused by temperature-dependent intrinsic properties of visual pigments such as the thermal equilibrium between active state Meta-II and its precursor Meta-I and/or the lifetime of Meta-II that may compete with the deactivation process consisting of phosphorylation by rhodopsin kinase (7).…”
supporting
confidence: 78%
See 3 more Smart Citations